Alkenylamides from Piper maingayi Hk. F - Ahmad, Farediah; Jamil, Shajarahtunnur; Ibrahim, Ahmed Zainudin; Read, Roger Wayne (Universiti Putra Malaysia Press, 1996)
Two unsaturated amides, N-isobutyl-9-phenyl-2E,4E,8E-nonatrienamide and N-isobutyl-7 (3', 4'-methylenedioxyphenyl)-2E,6E-heptadienamide, were isolated from the leaves of Piper maingayi. Both amides were characterized by spectral studies.